Principle and design of hatch operation system for fish migrating upstream-downstream of the discharge sill - Răzvan G.Voicu; Kelly N. Miles (Acta Scientiarum Polonorum. Formatio Circumiectus)
To improve fish migration and restore local lotic ecosystems, it is necessary to consider the various current hydro-construction methods. There have been partial successes in systems that improve fish passage over various obstacles but new approaches that present more efficient solutions and international collaboration among specialists are required. This article deals with European themes of great interest; issues related to interruption of longitudinal connectivity in heavily modified water courses, and improving the ecological status of damaged lotic systems, with the goal of achieving the environmental objectives set forth by the Water Framework Directive 2000/60/EC (WFD) and the national legislative framework regarding water policy (which reflects the European directives) Water Law no. 107, with subsequent amendments, NT No. / 2006 OM 1163/2007, and discusses the obligation to ensure that construction works protect fish migration to maintain ecological balance in the reservoirs. It is possible to use this system in almost any fish-bearing stream, both upstream and downstream of maximum circulation, which makes the system an excellent solution for assisting and improving migration.